5(-3x-2)-(x-3)=4(4x+5)+13

This encounters linear equations v one unknown.

You are watching: 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13


Step by action Solution

*

Rearrange:

Rearrange the equation by subtracting what is come the appropriate of the equal sign from both political parties of the equation : 5*(-3*x-2)-(x-3)-(4*(4*x+5)+13)=0

Step by action solution :

Step 1 :

Equation in ~ the end of step 1 :

((5•(-3x-2))-(x-3))-(4•(4x+5)+13) = 0

Step 2 :

Step 3 :

Pulling out like terms :3.1 pull out favor factors:-3x - 2=-1•(3x + 2)

Equation at the finish of action 3 :

(-5 • (3x + 2) - (x - 3)) - (16x + 33) = 0

Step 4 :

Step 5 :

Pulling out favor terms :5.1 traction out choose factors:-32x - 40=-8•(4x + 5)

Equation at the end of step 5 :

-8 • (4x + 5) = 0

Step 6 :

Equations i beg your pardon are never ever true:6.1Solve:-8=0This equation has actually no solution. A a non-zero consistent never equates to zero.

Solving a single Variable Equation:6.2Solve:4x+5 = 0Subtract 5 indigenous both sides of the equation:4x = -5 division both political parties of the equation through 4:x = -5/4 = -1.250

One systems was discovered :

x = -5/4 = -1.250


Why find out this

*

Terms and also topics

*

Related links

*

abc
a
x
y
/
|abs|
( )
7
8
9
*
4
5
6
-
%
1
2
3
+
0
,
.

See more: Pontoon Boat Speeds: How Fast Does A 40 Hp Pontoon Go ? How Fast Will A 40 Hp Pontoon Boat Go


=
abc
a
b
c
d
e
f
g
h
i
j
k
l
m
n
o
p
q
r
s
t
u
v
w
x
y
z

.
*

back to top